2020
DOI: 10.1080/12298093.2020.1823611
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium from Rhizosphere Soil in Terrestrial and Coastal Environments in South Korea

Abstract: Penicillium, the most common genus plays an important ecological role in various terrestrial and marine environments. However, only a few species have been reported from rhizosphere soil. As part of a project to excavate Korean indigenous fungi, we investigated rhizosphere soil of six plants in the forest (terrestrial habitat) and sand dunes (coastal habitat) and focused on discovering Penicillium species. A total of 64 strains were isolated and identified as 26 Penicillium species in nine sections based on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Similar findings were reported in previous studies ( Su et al, 2020 ; Liu L. et al, 2021 ; Varsadiya et al, 2021 ; Zheng et al, 2021 ). For instance, Penicillium plays a key role in rhizosphere soil, it can generate products that promote plant health (e.g., soluble phosphorus, iron carriers, plant hormones) and affect plant adaptability through a series of biochemical processes ( Altaf et al, 2018 ; Park et al, 2020 ). Further, Simplicillium has a wide range of hosts and substrates, which are associated with bioactive compounds and phytopathogens, and long-term continuous cultivation increases the relative abundance of Simplicillium ( Wei et al, 2019 ; Liu Q. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in previous studies ( Su et al, 2020 ; Liu L. et al, 2021 ; Varsadiya et al, 2021 ; Zheng et al, 2021 ). For instance, Penicillium plays a key role in rhizosphere soil, it can generate products that promote plant health (e.g., soluble phosphorus, iron carriers, plant hormones) and affect plant adaptability through a series of biochemical processes ( Altaf et al, 2018 ; Park et al, 2020 ). Further, Simplicillium has a wide range of hosts and substrates, which are associated with bioactive compounds and phytopathogens, and long-term continuous cultivation increases the relative abundance of Simplicillium ( Wei et al, 2019 ; Liu Q. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In detail, our results showed that Myrtus was characterised by a group of fungi composed mainly of Penicillium (soilinhabiting Penicillium), which are among the common producers of secondary metabolites in soil (Zhelifonova et al, 2010) and have an important function in the decomposition of organic matter (Frisvad & Samson, 2004). Park et al, (2020) found that most Penicillium species from soil are highly selective and unique to each plant. In our study, all shrubs do not form symbiosis with ectomycorrhiza, except Juniperus (Mejstrik & Cudlin, 1983), therefore, their presence under shrub canopies is in the form of free-living spores.…”
Section: Grassland Matrixmentioning
confidence: 99%
“…We explored fungal diversity from rhizosphere soil of various plants; Aspergillus, Penicillium, Trichoderma, and Fusarium were common genera. Recently, we reported on diversity of Penicillium, revealing eight unrecorded species in Korea [32]. The main purpose of this study was to focus on Aspergillus in the rhizosphere of various plants and to identify them based on BenA and CaM loci.…”
Section: Introductionmentioning
confidence: 99%